2019
DOI: 10.4317/jced.55026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propolis mouthwash on plaque and gingival indices over fixed orthodontic patients

Abstract: Background In patients with fixed orthodontics, the presence of orthodontic appliances causes dental plaque accumulation and hygiene problems. The purpose of this study was to evaluate the effect of Propolis and chlorhexidine mouthwashes on plaque and gingival indices in patients who are undergoing orthodontic treatment. Material and Methods In this triple blind study, in total, 37 patients aged from 15 to 35 years those who have been undergoing fixed orthodontic treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 15 publications
0
48
0
1
Order By: Relevance
“…General characteristics of the included studies are presented in Table 1 . Nine randomized clinical trials (RCT) involving 333 patients were included in this systematic review [ 8 , 11 , 14 , 17 22 ] (Table 1 ). Four studies were conducted in India [ 14 , 20 – 22 ], two in Brazil [ 17 , 18 ], one in Iran [ 11 ], one in Iraq [ 19 ], and one in the UK [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…General characteristics of the included studies are presented in Table 1 . Nine randomized clinical trials (RCT) involving 333 patients were included in this systematic review [ 8 , 11 , 14 , 17 22 ] (Table 1 ). Four studies were conducted in India [ 14 , 20 – 22 ], two in Brazil [ 17 , 18 ], one in Iran [ 11 ], one in Iraq [ 19 ], and one in the UK [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Medications or dentifrices known to affect the intervention were considered as exclusion criteria in all included studies. Three studies [ 11 , 17 , 21 ] reported excluding smokers, while the remaining studies did not provide any information about smoking status of the participants. The evaluation period ranged from 5 to 28 days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations